Effect of Attitude towards Mental Illness on Help-Seeking Behavior Among Adults: Moderating Role of Perceived Stigma - khan, Asad; Alyana, Dr. Sajid Iqbal (ACADEMIA International Journal for Social Sciences, 2025)
Attitudes toward mental illness and stigma play a critical role in determining whether individuals seek professional psychological help. In conservative and collectivist societies, negative attitudes and perceived stigma often discourage help-seeking.This study examined the effect of attitudes toward mental illness on help-seeking behavior among adults, and investigated perceived stigma as a moderator of this relationship.A cross-sectional design was employed with a sample of adults from the Pakhtoon community of Swat, Pakistan. Participants completed the Community Attitudes Toward the Mentally Ill (CAMI), the Stigma Scale, and the General Help-Seeking Questionnaire (GHSQ). Moderation analysis was conducted to examine the interactive effect of perceived stigma.Attitudes toward mental illness did not significantly predict help-seeking behavior. Perceived stigma did not moderate the relationship between attitudes and help-seeking behavior. No significant gender differences were observed in overall attitudes or help-seeking.Findings suggest that despite prevalent stigma, other sociocultural factors may play a stronger role in shaping help-seeking behavior. Culturally sensitive mental health interventions are needed.